Sistem Pakar dalam Identifikasi Kerusakan Gigi pada Anak dengan Menggunakan Metode Forward Chaining dan Certainty Factor - Dian, Rahmad; Sumijan, Sumijan; Yunus, Yuhandri (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
Tooth decay in children is one of the most common problems found. This damage has a long-term effect on children's dental health. The limitation of expert doctor's service hours and the disproportionate number of doctors and patients makes the service to patients not optimal. Then we need an expert system to help the role of expert doctors in diagnosing tooth decay. One of them carried out treatment or prevention measures from the start. In this study forward chaining and certainty factor methods are used, in which this expert system can assist an expert in diagnosing tooth decay based on the symptoms experienced by the patient. The forward chaining method will be collaborated with the certainty factor method to calculate the accuracy of the type of tooth decay experienced. The use of these two methods aims to provide better results in overcoming or preventing tooth decay in children. From the test results obtained knowledge for patients in dealing with or preventing tooth decay with an accuracy rate of 91.20%. The application of an expert system can be used for early action in overcoming or preventing tooth decay in children.